Evaluation and Public Policy: possibilities and challenges for Mathematics Education Avaliação e Políticas Públicas: possibilidades e desafios para a Educação Matemática - Maria Isabel Ramalho Ortigão (Universidade Estadual Paulista, 2008)
This text aims at assessing educational systems and curriculum, and seeks to promote thinking regarding the quality of education and the establishment of links between assessment, research and teaching of Mathematics in basic education. From data generated by the Sistema de Avaliação da Educação Básica (SAEB), we discuss the issue of quality in education based on indices associated with the efficacy e equality in schools. Subsequently, we assess the curriculum and touch upon research focused on the teaching of Mathematics in basic school. Finally, in addition to presenting a number of suggestions regarding the training of teachers, we conclude that beyond the need for how to teach, the training of Math teachers must take into consideration issues related to social and cultural differences that can significantly influence teaching and learning. Keywords: Assessment. Curriculum of Mathematics. Quality of Education. O texto aborda a avaliação de sistemas educacionais e a avaliação do currículo e procura contribuir para a reflexão sobre a qualidade da educação e para o estabelecimento de pontes entre a avaliação, a pesquisa e o ensino de Matemática na educação básica. A partir dos dados do Sistema de Avaliação da Educação Básica (SAEB), discute aborda o tema da qualidade da educação a partir de indicadores relacionados com a eficácia e a equidade das escolas. Em seguida, trata da avaliação de currículo e faz um breve apanhado das pesquisas que investigam o ensino de Matemática na escola básica. Finalmente, apresenta algumas sugestões para a discussão sobre a formação de professores, e conclui que, para além de discussões sobre o que e como ensinar, a formação do professor de Matemática precisa considerar questões sociais e culturais implicadas no ensino e na aprendizagem. Palavras-chave: Avaliação da Educação. Currículo de Matemática. Qualidade da Educação.